Study on ultrasonic detection method of a honeycomb sandwich panel. Issue 1 (1st February 2023) - Wang, Zhulin; He, Xiao
Abstract: A new material for the structure of the honeycomb sandwiched XinBi board has been in active service. In this paper, structural defects are embedded in the easily damaged parts of this new material, and the ultrasonic method is used to detect the easily damaged parts, and the acoustic signals and defect echo signals of the easily damaged parts are obtained, which provides a reference for damage evaluation of this kind of structures in site detection.